"In this place we have found sisterhood": perceptions of how participating in a peer-group club intervention benefited South African adolescent girls and young women. Issue 1 (1st January 2021) - Duby, Zoe; Verwoerd, Wilmé; McClinton Appollis, Tracy; Jonas, Kim; Maruping, Kealeboga; Dietrich, Janan J.; LoVette, Ashleigh; Kuo, Caroline; Vanleeuw, Lieve; Mathews, Catherine
ABSTRACT: A combination sexual and reproductive health (SRH) intervention for adolescent girls and young women (AGYW), implemented in South Africa 2016–2019, included facilitated peer-group clubs designed to build AGYW self-esteem, foster supportive peer networks, and provide SRH education. We conducted qualitative in-depth interviews and focus group discussions with AGYW who had participated in peer-group clubs, club facilitators, teachers and intervention implementers. Perceived benefits of participation in peer-group clubs included increased peer support, self-esteem, and gender empowerment, access to safe spaces, improved ability to access emotional support, and positive role modelling, which in turn contributed to improved well-being and mental health. Findings show that peer-group club interventions can be successful in promoting self-esteem, well-being and perceived social support amongst AGYW in South Africa. Given the protective role that social support and mental health have on positive SRH outcomes for AGYW, it is critical that combination interventions incorporate relevant and effective components.